The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ceramint.2017.07.089
|View full text |Cite
|
Sign up to set email alerts
|

High-performance and low-voltage SnO2-based varistors

Abstract: This paper presents the results of a thorough study conducted on the action mechanism of one-dimensional single-crystalline SnO 2 nanobelts in decreasing the breakdown electric field (E b) in SnO 2-based varistors. The proposed method has general validity in that our investigation was focused on the traditional varistor composition SnO 2-CoO-Cr 2 O 3-Nb 2 O 5. To accomplish our study objective, two methods of decreasing E b value were compared; one involving the increase in average grain size of the varistor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The alterations in grain boundary resistance caused by doping elements can significantly impact the nonlinear characteristics and leakage current of the varistors. 20,21 The values of the intersections far from the imaginary axis in the impedance diagram can be equivalent to the grain boundary resistance (R gb ) of the varistor. The grain boundary resistances for different samples are recorded in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alterations in grain boundary resistance caused by doping elements can significantly impact the nonlinear characteristics and leakage current of the varistors. 20,21 The values of the intersections far from the imaginary axis in the impedance diagram can be equivalent to the grain boundary resistance (R gb ) of the varistor. The grain boundary resistances for different samples are recorded in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the total impedance of the varistor are mainly attributed to alterations in the grain boundary resistance. The alterations in grain boundary resistance caused by doping elements can significantly impact the nonlinear characteristics and leakage current of the varistors 20,21 . The values of the intersections far from the imaginary axis in the impedance diagram can be equivalent to the grain boundary resistance ( R gb ) of the varistor.…”
Section: Resultsmentioning
confidence: 99%
“…A homogeneous dispersion of dopants over the entire volume of the varistor is crucial to obtain the same electrical properties in any direction. In the existing literature, it has been reported that there is a strong relationship between the quality of connections between each of the SnO 2 grains and the value of the coefficient α [20,21]. There are three main types of connections: ohmic, non-ohmic, and conductive.…”
Section: Resultsmentioning
confidence: 99%
“…1a shows the 2D growth of the belt after sintering for 2 h. The SEM image shows that the belt grew both laterally and vertically at the same proportion. Although different belts may present distinct growth rates based on the initial size, the belt has maintained their main role to eliminate shared grain boundaries and, thus, common potential barriers [22]. Consequently, there is no evidence of a more energetic interface, such as a faceted or a twin boundary, capable and responsible for stimulating their growth [13,23,24], raising the idea of a dominating coalescence growth mechanism.…”
Section: Methodsmentioning
confidence: 99%